Spatial navigation skills in older adults with and without cognitive impairment - Kossowska-Kuhn, Dorota; Prevratil, Michael J.; Charness, Neil; Boot, Walter R.; Czaja, Sara J.; Rogers, Wendy A. (Frontiers in Aging, 2025)
IntroductionNavigation is a fundamental cognitive ability essential for daily functioning. However, navigation skills decline with age and are further impaired in individuals with cognitive impairment (CI). Understanding these deficits is critical for developing interventions to support affected populations.MethodsThis study compared navigation abilities in older adults with CI (n = 20) to a previously collected community-dwelling sample of older adults (n = 380) using a consistent protocol. Both groups completed objective navigation tasks, subjective navigation assessments, and subjective memory evaluations.ResultsOlder adults with CI exhibited significantly lower performance on objective navigation tasks and subjective memory assessments compared to the community sample. Among the three subjective navigation measures, only one demonstrated a significant difference between the groups. Additionally, subjective navigation measures were not reliably predicted by subjective memory or objective navigation performance.DiscussionThese findings highlight a unique and complex relationship between navigation, aging, and cognitive impairment. The results underscore the need for further research to explore the effects of different types of CI on navigation and identify strategies to mitigate these deficits.ConclusionThis study provides valuable insights into navigation impairments associated with cognitive decline in aging populations, paving the way for targeted interventions to preserve navigation skills in affected individuals.